Biosurfactants: Promising Molecules for Petroleum Biotechnology Advances - De Almeida, Darne G.; Soares Da Silva, Rita de Cássia F.; Luna, Juliana M.; Rufino, Raquel D.; Santos, Valdemir A.; Banat, Ibrahim M.; Sarubbo, Leonie A. (Frontiers in Microbiology, 2016)
The growing global demand for sustainable technologies that improves the efficiency of petrochemical processes in the oil industry has driven advances in petroleum biotechnology in recent years. Petroleum industry uses substantial amounts of petrochemical-based synthetic surfactants in its activities as mobilizing agents to increase the availability or recovery of hydrocarbons as well as many other applications related to extraction, treatment, cleaning and transportation. However, biosurfactants have several potential applications for use across the oil processing chain and in the formulations of petrochemical products such as emulsifying/demulsifying agents, anticorrosive, biocides for sulphate-reducing bacteria, fuel formulation, extraction of bitumen from tar sands and many other innovative applications. Due to their versatility and proven efficiency, biosurfactants are often presented as valuable versatile tools that can transform and modernise petroleum biotechnology in an attempt to provide a true picture of state of the art and directions or use in the oil industry. We believe that biosurfactants are going to have a significant role in many future applications in the oil industries and in this review therefore, we highlight recent important relevant applications, patents disclosures and potential future applications for biosurfactants in petroleum and related industries.